Reliability of the system with loops: Factor graph based approach - Chae, Young Ho; Kim, Seung Geun; Seong, Poong Hyun (Reliability engineering & system safety, 2021)
•Factor graph based reliability analysis method is suggested.•To consider logical loop structure, modified belief propagation algorithm is suggested.•The result of factor graph based approach shows exactly same result as the analytic solution.•With suggested methodology, intuitive graph based reliability analysis can be conducted even if there exist logical loop structure. Evaluating systems’ vulnerability is important in safety critical systems. For this reason, probabilistic safety assessments (PSAs) are widely conducted in the nuclear industry. To ensure efficient, and accurate reliability analyses, several reliability evaluation methods have been developed. The most familiar method is fault tree analysis. However, as the system becomes more complex, the fault tree structure becomes even more complicated. As an alternative, the graph-based reliability analysis method has been developed. However, conventional graph-based analyses have difficulty with considering a logical loop structure. Here, we suggest a factor graph and belief propagation algorithm based logical loop analysis method for intuitive logical loop consideration. To solve the problem efficiently we modified the belief propagation rules. The proposed methodology was successfully applied to 3-system-in-loop and 4-system- in-loop.